Fully biobased biodegradable poly(l‐lactide)‐b‐poly(ethylene brassylate)‐b‐poly(l‐lactide) triblock copolymers: synthesis and investigation of relationship between crystallization morphology and thermal properties. Issue 4 (20th January 2020) - Jin, Chenhao; Leng, Xuefei; Zhang, Manwen; Wang, Yanshai; Wei, Zhiyong; Li, Yang
Abstract: Well‐defined poly(l ‐lactide‐ b ‐ethylene brassylate‐ b ‐l ‐lactide) (PLLA‐ b ‐PEB‐ b ‐PLLA) triblock copolymer was synthesized by using double hydroxyl‐terminated PEBs with different molecular weights. Gel permeation chromatography and NMR characterization were employed to confirm the structure and composition of the triblock copolymers. DSC, wide‐angle X‐ray diffraction, TGA and polarized optical microscopy were also employed to demonstrate the relationship between the composition and properties. According to the DSC curves, the cold crystallization peak vanished gradually with decrease of the PLLA block, illustrating that the relatively smaller content of PLLA may lead to the formation of a deficient PLLA type crystal, leading to a decrease of melting enthalpy and melting temperature. Multi‐step thermal decompositions were determined by TGA, and the PEB unit exhibited much better thermal stability than the PLLA unit. Polarized optical microscopy images of all the triblock samples showed that spherulites which develop radially and with an extinction pattern in the form of a Maltese cross exhibit no ring bond. The growth rate of the spherulites of all triblock samples was investigated. The crystallization capacity of PLLA improved with incorporation of PLLA, which accords with the DSC and wide‐angle X‐ray diffraction results. © 2019 Society of Chemical Industry Abstract : Fully biobased biodegradable poly(l ‐lactide)‐ b ‐poly(ethylene brassylate)‐ b ‐poly(l ‐lactide) triblock copolymers were synthesized and their crystallization morphology and thermal properties were investigated.